Pinus rarissima, a new species of the genus Pinus L. (Pinaceae) from central Vietnam - Velebil, Jiří; Businský, Roman; Tran, Toan Ngoc; Nguyen, Tran Quoc Trung; Luu, Hong Truong (Phytotaxa, 2025)
Probably the rarest pine species in the world, Pinus rarissima from central Vietnam, is described, illustrated and named, and its present-day distribution is characterized in detail. We classify it as a member of series Dalatenses (of the genus Pinus subgenus Strobus section Quinquefoliae subsection Strobus). It closely resembles P. dalatensis from the same series but also shares some features with P. anemophila from P. series Chylae subseries Wangianae. A thorough morphological comparison of the new pine species with similar taxa is presented, along with a key to the determination of pines of section Quinquefoliae occurring in Vietnam, Laos and southern China.